Study of a Water-Energy Integrated System: Challenges of Prototyping - Silva, Ana Rita (2018)
In a society where Energy and Water walk side by side in practically all sectors of activity, it becomes necessary to analyze them from a productive, economic and sustainable point of view. Although independently developed and regulated, it is known that water needs energy and energy needs water. The increasing demand for energy and its exponential trend will have repercussions at all levels in the short term. and consequently, will increase the strain on freshwater resources. All these concerns and associated decision-making policies create an opportunity to improve the management of both sectors. There is an urgent need to improve the water-energy system and reduce energy consumption, using advanced technological changes and an optimized management strategy, leading to a more sustainable future. By improving the efficiency of water and energy use through integrated smart strategies, there are very positive repercussions on savings and impact on the local economy, especially in decentralized cases. The present paper aims to address the theme of the nexus of water-energy in the scope of promoting alternatives of management and development of integrated systems and study the dynamics of the development of the theoretical concept vs. prototyping in case of urban context and real environment.